The problem of desulphurization of crude ferronickel obtained by low reduction technology at the Pobuzhsky ferronickel plant - Shevchenko , D.V.; Ovcharuk , A.M.; Nadtochiy , A.A. (Theory and Practice of Metallurgy, 2024)
Purpose. With the commissioning of the Canadian company Hatch’s RTP1 at the Pobuzhsky Ferronickel Plant and its transfer to low-reduction technology, it became possible to produce ferronickel containing only hundredths of a percent of silicon and carbon, which are necessary for soda desulfurization in a ladle. Therefore, the plant has implemented a comprehensive technology that provides for mixing (mixing) crude ferronickel produced from RTP1 with a reduced silicon and carbon content and a high Ni content, with an alloy from RTP2 with a low nickel concentration and a high silicon and carbon. However, due to the shutdown of RTP2 for major repairs, there was a need to develop a desulfurization mode using a combined scheme that involves combining soda desulfurization and oxygen-converter desulfurization, which is difficult and requires additional material and energy costs. Methodology. Thermodynamic modeling was performed using the HSC Chemistry 6.1 software package. Analytical and industrial research in the conditions of Pobuzhsky Ferronickel Plant. Results. The results of industrial research of the combined technological scheme of high-percentage ferronickel desulfurization in a ladle and converter were processed and analyzed, the technical results of ferronickel desulfurization at all stages of development and improvement of production in the conditions of the PFC were summarized. Scientific novelty. The equilibrium distribution of phases in the Fe-Ni-S-Na-Si-C-O system was carried out using the database of the HSC Chemistry 6.0 program. It was shown that silicon affects the completeness of the desulfurization reaction. The temperature limits of the process were identified. Practical significance. In industrial conditions of the Pobuzhsky Ferronickel Plant, a combined technology for desulfurization of high-grade ferronickel from RTP1 using the ladle-oxygen converter scheme has been developed and mastered, which has provided the possibility of the plant operating when RTP2 is stopped for major repairs and obtaining commercial products.